Corruption and trust in political institutions in sub-Saharan Africa - (:unkn) unknown (My University, 2008)
This paper analyzes the impact of corruption on the extent of trust in political institutions using a rich collection of comparable data provided by the Afrobarometer surveys conducted in 18 sub-Saharan African countries. More specifically, we set out to test the “efficient grease” hypothesis that corruption can strengthen citizens’ trust since bribe paying and clientelism open the door to otherwise scarce and inaccessible services and subsidies, and that this increases institutional trust. Our findings reject this theoretical argument. We show that corruption never produces trust-enhancing effects regardless of the evaluation of public service quality. The results reveal how perceived and experienced corruption impact negatively, but differently, on citizens’ trust in political institutions. The adverse effect of perceived corruption decreases with the fall in public service quality, whereas the negative effect of experienced corruption decreases as public service quality increases.
Keywords: African Research